(untitled) (World Economics and Finance Bulletin, 2024)
This study evaluated how financial leverage, firm size and profitability affects the value of quoted insurance companies (QICs) in Nigeria over the period 2010-2022. Secondary time-series were gathered from bias-free annual reports of 20 QICs. The unit root, Pedroni cointegration, and GMM techniques were adopted at the 5% level. The unit root test shows that all the variables are integrated at first difference leading to application of the Pedroni cointegration which confirmed the absence of long-run form among the variables. The GMM test shows that long-term debt and firm size are substantially positive to Tobin’s Q ratio; while short-term debt and ROE also promote the Tobin’s Q ratio, but this was seen to be insignificant. The study concludes that financial leverage and firm size are the two determinants of firm value among QICs in Nigeria. From the findings, the study advocates for the continual usage of long-term debt ratio and an increase in firm’s size of quoted insurance companies to accommodate more insurance businesses and at the same time boost the level of their confidence among potential and actual investors. Additionally, insurance companies are advised to do share buyback when analyzed to be undervalued to remain more competitive in their industry and create added value for shareholders. Lastly, the Central Bank of Nigeria should revert to a bi-monthly review of interest rate charges by lending institutions in Nigeria to help monitor and improve their performance on the usage of borrowed funds.